Virulence Gene- and Pandemic Group-Specific Marker Profiling of Clinical Vibrio parahaemolyticus Isolates - Meador, Carolyn E. (American Society for Microbiology, 2007)
Vibrio parahaemolyticus is a halophilic bacterium capable of causing food- and waterborne gastroenteritis, wound infections, and septicemia in humans. The organism has recently received increasing attention, as the emergence of a new clone, V. parahaemolyticus O3:K6, has resulted in the first documented pandemic spread of V. parahaemolyticus. We used microarray analyses to explore the presence of known virulence factors and genetic markers thought to be specific for V. parahaemolyticus O3:K6 and its clonal derivatives. Analyses of 48 human clinical isolates collected between 1997 and 2005 revealed that the V. parahaemolyticus chromosome 2 type III secretion system is not specifically associated with pandemic strains and can be found in tdh-negative (i.e., Kanagawa-negative) clinical isolates. These results highlight the genetic dynamism of V. parahaemolyticus and aid in refining the genetic definition of the pandemic group members.